The Effect of Leadership, Non-Physical Environment and Motivation on Employee Performance - Salam, Haris Hi Abd; Krisnandi, Herry; Digdowiseiso, Kumba (International Journal of Social Service and Research, 2024)
The purpose of this study was to determine the influence of leadership, work environment and motivation on employee performance at the Ministry of Religion of North Maluku Province in 2022. The research method used was an analytic survey with a cross-sectional research design. From the results of the study, it was found that the significance value of leadership was 0.004 < 0.05 and T arithmetic was 2.979 > T table (1.990), the significance value of the non-physical work environment was 0.005 < 0.05 and T calculated was 2.863 > T table (1.990) and the motivation significance value was 0.042 < 0.05 and T count of 2.071 > T table (1.990) so it can be concluded that there is an influence between leadership, non-physical non-work environment, and motivation with employee performance. It is hoped that the ministry of religion will increase good leadership and can try to use democratic and transformational types of leadership and build a good work environment by establishing good relationships between superiors and colleagues.